Relationship Between Speed and Time in Running - Hill, D. W.; Vingren, J. L.; Nakamura, F. Y.; Kokubun, Eduardo [UNESP] (Georg Thieme Verlag Kg, 2011)
The purpose of this study was to evaluate the effect of using different mathematical models to describe the relationship between treadmill running speed and time to exhaustion. All models generated a value for an aerobic parameter (critical speed; S(critical)). 35 university students performed 5-7 constant-speed 0%-slope treadmill tests at speeds that elicited exhaustion in similar to 3 min to similar to 10 min. Speed and time data were fitted using 3 models: (1) a 2-parameter hyperbolic model; (2) a 3-parameter hyperbolic model; and (3) a hybrid 3-parameter hyperbolic + exponential model. The 2-parameter model generated values for S(critical) (mean (+/- SD): 186 +/- 33 m.min(-1)) and anaerobic distance capacity (ADC; 251 +/- 122 m) with a high level of statistical certainty (i.e., with small SEEs). The 3-parameter models generated parameter estimates that were unrealistic in magnitude and/or associated with large SEEs and little statistical certainty. Therefore, it was concluded that, for the range of exercise durations used in the present study, the 2-parameter model is preferred because it provides a parsimonious description of the relationship between velocity and time to fatigue, and it produces parameters of known physiological significance, with excellent confidence.
Keywords: aerobic; anaerobic; critical power; critical velocity; mathematical; model